2013
DOI: 10.1094/pdis-11-12-1100-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of a 16SrIX Group (Pigeon Pea Witches'-Broom) Phytoplasma Associated with Sesame Phyllody in Turkey

Abstract: Sesame (Sesamum indicum L.) is an important oilseed crops widely grown in the southern regions of Turkey. Sesame seeds are primarily used in production of tahini as well as a garnish on sweets and bakery products in the country. Sesame plants with phyllody disease symptoms have increasingly been observed in the fields of Antalya province since 2007. The disease incidence in these fields was found to range from 37 to 62% (2). Infected plants display a variety of the disease symptoms such as virescence, asymptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…The results clearly revealed that the sesame phyllody disease was caused by phytoplasma and it is transmitted only by leafhopper, Orosius albicinctus and the stem of symptomless branch of infected plant also harbor phytoplasma. Similar results were also obtained by Al-Sakeiti et al (2005), Akhtar et al (2009) and Catal et al (2013) in different places by using same primer pairs from the infected sesame plants. However, Sertkaya et al (2007) detect phytoplasma from both infected plants and its vector Orosius orientalis (Matsumura) by using the universal phytoplasma primer pair P1/P7 in direct PCR followed by primer pair R16F2n/R16R2 in nested PCR in Turkey.…”
Section: Resultssupporting
confidence: 89%
“…The results clearly revealed that the sesame phyllody disease was caused by phytoplasma and it is transmitted only by leafhopper, Orosius albicinctus and the stem of symptomless branch of infected plant also harbor phytoplasma. Similar results were also obtained by Al-Sakeiti et al (2005), Akhtar et al (2009) and Catal et al (2013) in different places by using same primer pairs from the infected sesame plants. However, Sertkaya et al (2007) detect phytoplasma from both infected plants and its vector Orosius orientalis (Matsumura) by using the universal phytoplasma primer pair P1/P7 in direct PCR followed by primer pair R16F2n/R16R2 in nested PCR in Turkey.…”
Section: Resultssupporting
confidence: 89%
“…Sesame plants affected by phytoplasma showed symptoms of floral virescence, phyllody, stem fasciation, shortened internodes and cracking of seed capsules (Figure j). Sesame phyllody has been reported to be caused by different groups of phytoplasma, that is group 16SrI in India (Khan, Raj, & Snehi, ), Myanmar (Win, Back, & Jung, ) and South Korea (Lee et al., ); group 16SrII in India (Pamei & Makandar, ), Iran (Esmailzadeh‐Hosseini, Mirzaie, Jafari‐Nodooshan, & Rahimian, ), Oman (Al‐Sakeiti, Al‐Subhi, Al‐Saady, & Deadman, ), Pakistan (Akhtar et al., ), Taiwann (Tseng, Deng, Chang, Huang, & Jan, ), Thailand (Martini et al., ) and Turkey (Ikten et al., ); group 16SrVI in Turkey (Sertkaya, Martini, Musetti, & Osler, ); group 16SrIX in Iran (Salehi, Heydarnejad, & Izadpanah, ) and Turkey (Catal, Ikten, Yol, Ustun, & Uzun, ); and subgroup 16SrIX–C in Turkey (Ikten et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…in Iran (Salehi, Heydarnejad, & Izadpanah, 2005) and Turkey (Catal, Ikten, Yol, Ustun, & Uzun, 2013); and subgroup 16SrIX-C in Turkey (Ikten et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The probes 16SrII and 16SrIX were designed from the sequences between these primer pairs for specific detection of 16Sr group II and group IX phytoplasmas, respectively, in TaqMan ® qPCR assay. Representative sequences of 16Sr groups I through XIV [ 47 , 48 , 49 ] ( S1 Fig ) including sesame phyllody 16Sr groups II and IX [ 39 , 40 ] were aligned to design the primer and probes ( Fig 1 ). The sequences of all phytoplasma groups available in the National Center for Biotechnology Information (NCBI) GenBank database were also included in the alignments.…”
Section: Methodsmentioning
confidence: 99%
“…Sesame phyllody, an economically important disease of sesame plants, is a serious threat in regions where peanut witches’ broom (16SrII) [ 9 , 12 , 38 , 39 ], pigeon pea witches’ broom (16SrIX) [ 40 ], aster yellows (16SrI) [ 41 , 42 ], and clover proliferation (16SrVI) [ 14 ] phytoplasmas are present. Although four different phytoplasma groups have been reported in sesame so far, the majority (approximately 77%) of identified sesame phytoplasmas have been known to belong to the 16SrII and 16SrIX groups [ 43 ].…”
Section: Introductionmentioning
confidence: 99%